Sexual habits and social factors in local Ghanaian prostitutes which could affect the spread of Human Immu- nodeficiency Virus (HIV) - Neequaye, I.E.; Neequaye, A.R.; Mingle, I.A.; Ofori-Adjei, D.; Osei- Kwasi, M.; Grant, F.; Hayami, M.; Ishikawa, R.J.; Biggar, R.J. (Ghana Medical Journal, 1987)
One hundred and sixteen prostitutes working locally in Accra (Tema were interviewed as to their sexual habits. A major finding was that only one used condoms regularly. The average number of clients was 3-4 per week in the higher socio-economic status group and 16 per week in the lower socio-economic class. Less than 1% were positive for HIV infection in February 1986 and 0% of 241 blood donors were positive. These findings indicated that the HIV infection rate was still very low and a preventive education campaign could be effective in reducing the spread of the disease into Ghana.
Journal Article
Keywords: prostitutes; sexual habits; HIV infection rate; Ghana